UN Convention on the Rights of the Child: Protection - Lis, Wojciech (International Children's Rights, 2024)
The child requires to be surrounded by protection by adults, whose duty it is to create an optimal environment for the child to live and develop. These actions serve to realize the welfare of the child, which is a fundamental objective of the provisions of the Convention on the Rights of the Child and other normative acts. The protection of the child’s well-being is served by the rights of the child, which emphasize the child’s subjectivity as a result of being human. A person’s age cannot be a discriminatory criterion in the exercise of freedoms and rights. The best interests of the child guide the interpretation of provisions and the application of the law. At the international level, the Committee on the Rights of the Child plays a special role in this regard, and presents its views on the protection of children’s rights through its general comments on the provisions of the CRC. The main purpose of the paper is to try to identify child protection options through the lens of general comments containing the position of the Committee on the Rights of the Child on how to understand the provisions on the protection of the child from all forms of violence and the obligations of states parties to the CRC in implementing its provisions in the practice of national authorities. Keywords: child protection, children’s rights, general comments, violence against, the child, risks of the digital world, preventive action